2016
DOI: 10.1016/j.apor.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

High-fidelity CFD simulation of wave run-up for single/multiple surface-piercing cylinders in regular head waves

Abstract: a b s t r a c tThe capabilities of CFDShip-Iowa V4.5 and V6.2 simulations for wave run-up for single/multiple surface-piercing cylinders in regular waves are assessed in conjunction with the ITTC OEC Workshop on VIV and Wave Run-up held in Nantes, France October 17-18, 2013. Statistical convergence and grid/domain/turbulence model sensitivity studies show uncertainty U I values are less than 1% for both the experiment/simulation data and grid/domain/turbulence model sensitivities are less than the facility bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…When K c < 3, the flow is inertia dominated, and the effects of boundary-layer separation and vorticity are small (e.g. Sumer 2006;Yoon et al 2016;Mohseni et al 2018). All of our simulations are in this regime (cf.…”
Section: Appendix B Convergence Of the Hybrid Numerical Model (Qalefoam)mentioning
confidence: 84%
“…When K c < 3, the flow is inertia dominated, and the effects of boundary-layer separation and vorticity are small (e.g. Sumer 2006;Yoon et al 2016;Mohseni et al 2018). All of our simulations are in this regime (cf.…”
Section: Appendix B Convergence Of the Hybrid Numerical Model (Qalefoam)mentioning
confidence: 84%
“…RANS (Reynolds Averaged Navier-Stokes) simulations have been conducted to study wave run-up of a single circular cylinder in regular waves by Kim and Lee (2014) and experimental results were compared with numerical ones. Yoon et al (2015) showed wave run-up phenomena around single/multiple surface piercing circular cylinders in regular head waves using the lab developed in-house CFD codes. Cha et al (2016) investigated the wave runup height around single and multiple surface-piercing cylinders according to wave period and steepness using numerical methods.…”
Section: Introductionmentioning
confidence: 99%